Assessing exploitation status of Caspian roach (Rutilus caspicus, Yakovlev, 1870) in southeast of the Caspian Sea - R. dordi Tatr; R. Ghorbani; S. Gorgin; Gh. Bandani; M. Yahyaei (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 2018)
Caspian roach (Rutilus caspius), is one of the most important commercial species in the Caspian Sea with a high level of catch fluctuations over the past decades mainly due to overfishing. In this study, data from 246 specimens caught from beach seine cooperative companies in the southeast coast of the Caspian Sea during the October 2014- April 2015 were analyzed. Results showed that the fish age were ranged between 3 to 10 years with fork lengths and weights ranging 14.5-32.1 cm and 70.7-437 g, respectively. The growth parameters of the von Bertalanffy equation were found as Lt=41.8 [1-e–0.12(t+0.766)]. The length-weight relationships were estimated to be WT= 0.0208 FL2.9184 (R2 =0.901) for females and WT= 0.0138 FL3.0244 (R2 =0.921) for males. Weight increased isometrical with the fork length for females and males. Total mortality, natural and fishing coefficients (Z, M, F) and exploitation rate (E) were estimated to be 1.239, 0.324, 0.916 year-1 and 0.74, respectively. Fish biomass and maximum sustainable yield (MSY) were equal to 417 Kg and 215 Kg, while the ration of cooperative companies catch was 28 Kg. Therefore, it is suggested that the Caspian roach stocks are severely exposed to overfishing, and there is an urgent need to efficient management for stock conversation